RELIGIOUS PRACTICES VIS-A-VIS NOISE POLLUTION: CHURCH OF GOD (FULL GOSPEL) IN INDIA v. K.K. R. MAJESTIC COLONY WELFARE ASSOCIATION AND OTHER - A Comment (NATIONAL CAPITAL LAW JOURNAL, 2026)
NA
Keywords: Noise Pollution; Religious Freedom; Environmental Protection; Public Nuisance; Freedom Of Religion; Right To Life; Environmental Jurisprudence; Environmental LAW; Jurisprudence; Noise Regulation Rules; Public Health; Constitutional Rights.